Performing multilingualism on the Caroline stage in the plays of Richard Brome - Paravano, Christina (Cambridge Scholars Publishing, 2018)
The book investigates the issue of multilingualism in the Caroline age through the lens of Richard Brome's theatre. It analyses Brome's multilingual representation of early modern London between 1625 and 1642, a multilingual and cosmopolitan city, a pole of attraction, a crossroads of religious, linguistic, political, and cultural experiences in a national and European context. The interaction between English and foreign languages has always been a sort of obsession for early modern England but, in this specific period, its role becomes increasingly important: interpreting this delicate, and un.